AUDIT FEE: EVIDENCE FROM INDONESIAN LISTED COMPANIES - ANDRIVAN NINDYA KRISNA, 041411331172 (2018)
This research is intended to obtain the empirical evidence of determinants that affects the external audit service fee. Using the modified model from research of Simunic (1980), this research took balanced samples from 26 manufacturing firms of Indonesian Stock Exchange (IDX) from 2014 to 2016 in order to represent the population of all manufacturing firms in that period. Using audit fee as dependent variable and firm size, audit complexity, audit risk, and Big-Four audit firms’ premium, this research tried to find out the relationship between those variables, using multiple linear regression as the method to achieve that goal. The result of this research proven that firm size, audit complexity, audit risk, and Big-Four audit firms’ premium positive and significantly affect the audit fee.